Contextual strategies to support social inclusion for children with and without disabilities in recreation. Issue 11 (22nd May 2021) - Edwards, Brydne M.; Cameron, Debra; King, Gillian; McPherson, Amy C.
Abstract: Purpose: Integrating children with and without disabilities in recreation programs is assumed to promote inclusion. How social inclusion is facilitated in recreation settings, however, is not fully known. This study aimed to explore how social inclusion is supported in a recreation program. Materials and methods: A generic qualitative methodology was adopted. Seventeen children with and without disabilities registered for the same program were recruited. This sample included eight children with disabilities and nine typically developing children between the age of eight and 17. Two semi-structured interviews and three, two-hour observation periods were conducted with each participant. Inductive thematic analysis was used to analyze interview and observation data. Results: This study revealed five themes that support meaningful aspects of social inclusion from participants' perspectives: (a) creating opportunities for children to communicate their interests and desires; (b) providing opportunities to choose self-directed activities; (c) strategically selecting and placing objects to support interactions between children with and without disabilities; (d) directly encouraging interactions between children with and without disabilities, and; (e) Having relatively equal numbers of children with and without disabilities. Conclusions: This study facilitates a better understanding of how meaningful inclusion experiences can be facilitated in recreation settings. Implications for rehabilitation: Participation in recreation programs that implement inclusive strategies could mitigate social isolation and loneliness for children with disabilities. Children with and without disabilities may experience greater sense of inclusion when recreation programs adopt a process-oriented and child-driven approach. Staff play a critical role in implementing inclusive strategies such as establishing group communication competency between children with and without disabilities, which could be supported by staff training.